Passive Stiffness Modification of a Seismically Isolated Bridge Deck under Seismic Excitation - Yanik, Arcan; Aldemir, Unal (Journal of Strategic Innovation and Sustainability, 2018)
This study is on the seismic performance assesment of a seismically isolated bridge structure with passive stiffness modification implementation. Performance of the passive stiffness modification approach is compared with semi-active control implementation on the bridge deck. El Centro NS(north-south) and Kobe EW(east-west) eartquake excitations are used for the dynamic simulations of the passive case. Results are given in a comparative way for the uncontrolled bridge deck, passive stiffness modification implemented and semi-actively controlled, seismically isolated bridge deck (Yanik & Aldemir, 2018). Frequency dependent acceleration, velocity and displacement response transmissibility ratios are defined to examine the results.